Myelin protein zero mutations and the unfolded protein response in Charcot Marie Tooth disease type 1B. Issue 4 (10th March 2018) - Bai, Yunhong; Wu, Xingyao; Brennan, Kathryn M.; Wang, David S.; D'Antonio, Maurizio; Moran, John; Svaren, John; Shy, Michael E.
Abstract: Objective: To determine the prevalence of MPZ mutations that cause Charcot Marie Tooth neuropathy type 1B (CMT1B) and activate the unfolded protein Response (UPR). Background: CMT1B is caused by >200 heterozygous mutations in MPZ, the major protein in peripheral nerve myelin. Mutations Ser63del MPZ and Arg98Cys MPZ cause the mutant protein to be retained in the ER and activate the generally adaptive UPR. Treatments that modulate UPR activation have improved cellular and rodent models of CMT1B raising the possibility that other MPZ mutations that activate the UPR would also respond favorably to similar treatment. The prevalence of MPZ mutations that activate the UPR is unknown. Methods: We developed a dual luciferase reporter assay of Xbp1 splicing using stably transfected RT4 Schwann cells to assay the ability of cDNA constructs bearing 46 distinct MPZ mutations to activate the UPR. Constructs also carried an HA tag to permit detection of ER retention of mutant proteins. UPR activation and ER retention were correlated with clinical phenotypes. Results: Eighteen mutations demonstrated ER retention and UPR activation to a similar degree as Ser63del and Arg98Cys MPZ. Thirty‐five of the mutations activated the UPR > 1.5 fold compared to that of wild‐type MPZ. Correlation was high between firefly and Nano‐luciferase reporters and between both reporters and ER localization. UPR activity did not correlate with clinical onset or severity. Conclusion: Many CMT1B causing mutations activate the UPR and may be susceptible to therapeutic efforts to facilitate UPR function.